Bibliografijos teorijos sąvoka ir struktūra - Janonis, Osvaldas (Knygotyra, 1988)
M. Briskman’s, E. Bespalova’s, O. Korshunov’s, and L. Lelikova’s viewpoints on the concept of the theory of bibliography are examined. The theory of bibliography should be more strictly differentiated from other kinds of scientific information. The author considers the theory of bibliography to be the highest level of scientific information. O. Korshunov’s general theory of bibliography meets this requirement. The article discusses the structure of the theory of bibliography and their interrelations.